2001
DOI: 10.1038/ni739
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tapr (an airway hyperreactivity regulatory locus) and the linked Tim gene family

Abstract: To simplify the analysis of asthma susceptibility genes located at human chromosome 5q23-35, we examined congenic mice that differed at the homologous chromosomal segment. We identified a Mendelian trait encoded by T cell and Airway Phenotype Regulator (Tapr). Tapr is genetically distinct from known cytokine genes and controls the development of airway hyperreactivity and T cell production of interleukin 4 (IL-4) and IL-13. Positional cloning identified a gene family that encodes T cell membrane proteins (TIMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
433
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(444 citation statements)
references
References 57 publications
9
433
1
1
Order By: Relevance
“…14 Tapr, a locus that regulates mouse airway hyperreactivity and Th2 differentiation, has also been identified in a similar region using chromosome 11 congenic mice, which were derived from BALB/c and DBA/2. 30 These findings are not inconsistent with our own. It is possible that the genetic contributions from chromosome 11 loci are strain specific and did not contribute sufficient phenotype dosage, relative to Tsi1-3, to become apparent in our experimental cross.…”
Section: Discussionsupporting
confidence: 65%
“…14 Tapr, a locus that regulates mouse airway hyperreactivity and Th2 differentiation, has also been identified in a similar region using chromosome 11 congenic mice, which were derived from BALB/c and DBA/2. 30 These findings are not inconsistent with our own. It is possible that the genetic contributions from chromosome 11 loci are strain specific and did not contribute sufficient phenotype dosage, relative to Tsi1-3, to become apparent in our experimental cross.…”
Section: Discussionsupporting
confidence: 65%
“…However, this amino acid change (Q291L) is not at a critical site for carbohydrate recognition [17]. It has been reported that seven amino acid variations exist between the extracellular Ig domain of TIM-3 in different mouse strains [18] and that these variations may be involved in differential regulation of the Th1 response. BALB/c mice, which tend to develop Th2-biased immune responses with enhanced airway hyperreactivity, have different TIM-3 alleles than do C57BL/6 and DBA/2 mice that have Th1-prone immunity.…”
Section: Resultsmentioning
confidence: 99%
“…30 The TIM gene family includes three members (Tim-1, Tim-3 and Tim-4) in humans and eight members (Tim-1 to Tim-8) in mice. 31 Due to its unique structure, the TIM gene family is thought to participate in the regulation of immunological processes.…”
Section: Discussionmentioning
confidence: 99%